Depth distribution and ecological preferences of periphytic algae in Kenyir Lake, the largest tropical reservoir of Malaysia - Rouf, A.J.M.A.; Phang, Siew Moi; Ambak, M.A. (Science Press, 2010)
We studied the depth distribution of periphyton, growing on inundated dead trees in Kenyir Lake, Malaysia in June 1995. The algal floral composition and structure manifested changes down the depth gradient in terms of species richness, abundance, diversity and cell density. In regression analysis, all these algal attributes were negatively correlated with the depth gradients at P < 0.05. In terms of species richness, the bacillariophytes showed dominance over the cyanophytes and chlorophytes; whereas with respect to standing crop, the cyanophytes showed dominance over the bacillariophytes and chlorophytes. The chlorophyll a was higher at the mid and bottom-depths than the surface-depth in both the downstream and upstream sites, which showed that vertical productivity or biomass accumulation was greater in low light irradiance. The product-moment correlation analysis showed that conductivity, turbidity, dissolved oxygen, reactive phosphate and ammonium-nitrogen were highly correlated with the algal assemblage data. However, photosynthetic active radiation (PAR) showed poor correlation with the community data. These observations have cast some light on the autoecological characteristics, habitat preferences and environmental responses of tropical periphytic communities.